Aïm Deüelle Lüski and horizontal photography - Azulai, Ariʾelah 1962- (Leuven Univ. Press, 2014)
This book is the product of a unique collaboration between Israeli artist and philosopher Aïm Deüelle Lüski and visual culture theorist Ariella Azoulay. In their longstanding working relationship, they research how to theorize the structure of the contemporary scopic regime and open a space for its civil transformation. On this occasion, Azoulay interprets a particular series of cameras built by Deüelle Lüski, along with photographs taken by these cameras. Unlike conventional cameras and their vertical photography, Deüelle Lüski's cameras seek to generate new sets of relations between the camera and the world. Azoulay's text unfolds four different "short histories" of problems in photography, each of which deconstructs what otherwise might appear as a coherent photographic regime, yet which is shown to be based solely on principles of sovereignty and possession. Through and with Deüelle Lüski's project Azoulay seeks to "potentialize" the history of photography, that is, to recover long forgotten, un-materialized possibilities
Keywords: Deʿuʾel Lusḳi, Ḥayim -- ca. 20./21. Jh.